Self-compassion dan Subjective Well-being Remaja Tunadaksa - Ulifa Rahma; Rekyan Puspitasari (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2019)
Adolescents with physical disability is an adolescents whose have bodily abnormalities in their structure or function which can interfere with their activities such as normal teenagers. The psychological impact suffered by adolescents with physical disability such as low self-esteem, anxiety, frustration, withdrawal from society and apathy. Those condition can reduce the level of subjective well-being and to improve there is internal factors, self-compassion. This research has the aim of knowing how the relationship of self-compassion towards subjective well-being of adolescents with physical disability. This research use quantitative correlational with 140 total sample. The results shows that there is a significant relationship self-compassion toward subjective well-being. Relationships have a positive direction, when self-compassion increased, subjective wellbeing also higher in adolescent with physical disability and vice versa.